2022
DOI: 10.1101/2022.08.11.503474
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accurate localization and coactivation profiles of the Frontal Eye Field and Inferior Frontal Junction: an ALE and MACM fMRI meta-analysis

Abstract: The frontal eye field (FEF) and the inferior frontal junction (IFJ) are prefrontal structures involved in mediating multiple aspects of goal-driven behavior. Despite being recognized as prominent nodes of the networks underlying spatial attention and oculomotor control, and working memory and cognitive control, respectively, the limited quantitative evidence on their precise localization has considerably impeded the detailed understanding of their structure and connectivity. In this study, we performed an acti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 247 publications
(575 reference statements)
0
1
0
Order By: Relevance
“…More specifically, the DLPFC and neighbouring regions in the prefrontal cortex have a crucial role in goal-driven behaviour. Through complex structural and functional connectivity patterns across higher order frontal, parietal, and temporo-parietal regions, the DLFPC exerts top-down and bottom-up modulations of attention (e.g., influencing the balance between the ventral and dorsal attention networks), encodes working memory signals, and maintains and updates behavioural goals according to internal representations 17 , 21 . While the DLPFC’s role in mind-wandering is less well-characterised, a recent study revealed increased activity in this area during “off-task” periods in a non-demanding 0-back task 22 .…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the DLPFC and neighbouring regions in the prefrontal cortex have a crucial role in goal-driven behaviour. Through complex structural and functional connectivity patterns across higher order frontal, parietal, and temporo-parietal regions, the DLFPC exerts top-down and bottom-up modulations of attention (e.g., influencing the balance between the ventral and dorsal attention networks), encodes working memory signals, and maintains and updates behavioural goals according to internal representations 17 , 21 . While the DLPFC’s role in mind-wandering is less well-characterised, a recent study revealed increased activity in this area during “off-task” periods in a non-demanding 0-back task 22 .…”
Section: Introductionmentioning
confidence: 99%